Intervention of Hydration Protocol on Strength, Endurance, and Muscle Power Performance - Ramadhan, Wahyu Syahrul; Lubis, Leonardo; Oktavia, Nandina; Womsiwor, Daniel; Tarigan, Beltasar (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
WaterÂ is a molecule that plays an essential role in the muscle contraction process because muscle is a tissue that mostly contains water (75-80%). Therefore, athletes need to maintain fluid intake to support their physical activities when competing and when training. Nevertheless, in several studies, it was noted that some athletes experienced hypohydration or dehydration, which ultimately impaired muscle performance. Therefore, this study was conducted to determine the hydration protocol intervention on muscle strength, endurance, and power performance. This research is an analytical study with quasi-experimental research methods, namely single-arm pre-post study design using secondary data. Subjects of this study were 69 athletes year 2020 (named consecutively: Muaythai 9, Pencak silat 12, wrestling 10, judo 18, and taekwondo 20 athletes). This research was conducted from December 2019 to January 2020. In the beginning, all athletes were tested for muscle strength using a leg dynamometer, then muscle endurance tests using push-up and sit-up tests, and muscle power tests using the triple hop test of the right and left legs. After the first test, all athletes were educated about the hydration protocol. The hydration protocol was determined based on each athlete's sweat rate (ISR) and the training characteristics of each sports division. Then, all athletes underwent the training for two months. After that, the same tests were performed. The result showed that hydration protocol influenced the performance of muscle strength, endurance, and power. Therefore, the hydration protocol is influential in maintaining a good hydration status in athletes so that the athlete does not experience hypohydration which will later impair the athlete's muscle performance. Therefore, it is crucial to apply hydration protocols individually according to the training program (volume of training), not only in martial arts sports but in all sports.